Pengembangan Agrowisata Berbasis Masyarakat Di Desa Lamajang Kabupaten Bandung - Titing kartika; emron edison (PolimdoSains, 2021)
Lamajang Village, Bandung Regency has 5.5 ha of agricultural land and Animal Husbandry which is managed directly by the community. These farms include fruits, vegetables, medicinal plants, others, having sheep, chicken, fish and pigeon farms. This research was conducted to find out what agrotourism activities could be carried out, to what extent agrotourism had been developed, and to know the role of the community in agrotourism activities. The research method used is a qualitative research method. Data collection techniques were carried out by means of observation, interviews, and documentation studies, primary data sources were obtained from people who work in agriculture and secondary data sources were directly collected by researchers as support from the first source. The results showed that the Oldjang Village agrotourism has a fairly good agricultural potential. However, there is no mapping, understanding of the concept of agrotourism and the absence of facilities that support Agro-tourism Development in Lamajang Village.